Electronic excitation to low-lying states of GeF4 molecule by electron impact: A comparative study with CF4 and SiF4 molecules. (August 2015) - Ohtomi, S; Matsui, M; Mochizuki, Y; Suga, A; Kato, H; Hoshino, M; Duflot, D; Limão-Vieira, P; Tanaka, H
Synopsis: We report on the measurements of the electron impact electronic excitation cross sections for XF4 (X = C, Si and Ge) molecules at 100 eV, 5° scattering angle and 30 eV, 30° in the electron energy loss range 8.0 - 18 eV. For a target of GeF4 molecule, the optically-forbidden behavior has been observed in the lower electron energy loss range.